Embolization of Nonvariceal Upper Gastrointestinal Hemorrhage Complicated by Bowel Ischemia - Foltz, Gretchen; Khaddash, Tamim (Seminars in Interventional Radiology, 2019)
Over the past three decades, transcatheter arterial embolization has become the first-line therapy for the management of acute nonvariceal upper gastrointestinal bleeding refractory to endoscopic hemostasis. Overall, transcatheter arterial interventions have high technical and clinical success rates. This review will focus on patient presentation and technical considerations as predictors of complications from transcatheter arterial embolization in the management of acute upper gastrointestinal hemorrhage.
Keywords: upper gastrointestinal hemorrhage; angiography; transcatheter arterial embolization; complication rates; bowel ischemia; interventional radiology